First-Principles Study of Electronic and Dielectric Properties in Lanthanum Manganate - Omkar, H. S.; Sreepad, H. R. (Asian Journal of Science and Applied Technology, 2019)
First-principles calculations based on Density Functional Theory have been done on Lanthanum manganate. Its orthorhombic unit cell has been simulated. Electronic density of states has been computed and it shows that the material shows the nature of semiconducting material with a band gap of 1.38eV. Dielectric constant and Polarizability of the material have been computed. The value of dielectric constant comes out to be 47.3, 13.3 and 15.2 along X, Y and Z axes respectively with an average value of 25.3. The polarizability values are found to be 55.1(Å)3, 47.2(Å)3 and 48.5 (Å)3 along X, Y and Z axes respectively with an average value of 50.3(Å)3. Phonon modes at gamma point in the material range from 0 cm-1 to 885 cm-1.